2021
DOI: 10.1002/adma.202008560
|View full text |Cite
|
Sign up to set email alerts
|

General Design Methodology for Organic Eutectic Electrolytes toward High‐Energy‐Density Redox Flow Batteries

Abstract: By virtue of strong molecular interactions, eutectic electrolytes provide highly concentrated redox‐active materials without other auxiliary solvents, hence achieving high volumetric capacities and energy density for redox flow batteries (RFBs). However, it is critical to unveil the underlying mechanism in this system, which will be undoubtedly beneficial for their future research on high‐energy storage systems. Herein, a general formation mechanism of organic eutectic electrolytes (OEEs) is developed, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…[44] Organic-based eutectic electrolytes, are a class of the facile eutectic system to boost the concentration of metal and organic active components given interactions effects, and additionally, an excellent exhibition of low vapor pressure and thermosta-bility heighten practical implementation. [89] Representatively, the low-cost DES using urea and ChCl with a stoichiometric ratio of 2:1 shows good solubility for various Zn salts [e.g., Zn sulfate (ZnSO 4 ), ZnCl 2 , Zn nitrate (Zn(NO 3 ) 2 ), and Zn acetate (Zn(Ac) 2 )], high ionic conductivity, and a wide electrochemical window (Figure 5c). The resulting eutectic electrolytes optimize the solvation structures of Zn ions in the electrolyte and allow dendrite-free Zn stripping/plating over 3920 h for Zn-S batteries.…”
Section: Nonaqueous Eutectic Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Organic-based eutectic electrolytes, are a class of the facile eutectic system to boost the concentration of metal and organic active components given interactions effects, and additionally, an excellent exhibition of low vapor pressure and thermosta-bility heighten practical implementation. [89] Representatively, the low-cost DES using urea and ChCl with a stoichiometric ratio of 2:1 shows good solubility for various Zn salts [e.g., Zn sulfate (ZnSO 4 ), ZnCl 2 , Zn nitrate (Zn(NO 3 ) 2 ), and Zn acetate (Zn(Ac) 2 )], high ionic conductivity, and a wide electrochemical window (Figure 5c). The resulting eutectic electrolytes optimize the solvation structures of Zn ions in the electrolyte and allow dendrite-free Zn stripping/plating over 3920 h for Zn-S batteries.…”
Section: Nonaqueous Eutectic Electrolytesmentioning
confidence: 99%
“…Notably, we believe the versatile types and functionalities of eutectic electrolytes efficiently bridge the accelerated development of other energy storage devices (i.e., sodium, calcium, aluminum, and magnesium-based batteries/SCs) in the future. [89,103]…”
Section: Perspectivesmentioning
confidence: 99%
“…The diversity in molecular structure and elemental abundance of organic molecules provide great opportunities for designing high-performance OEEs [40][41][42][43][44][45][46][47] . By mixing EG, malonic acid, and viologen-based ammonium salt, Goeltz et al 42 obtained a metalfree low melting point OEE with viologen concentration as high as 4.2 mol•L −1 .…”
Section: Eutectic Electrolytementioning
confidence: 99%
“…Recently Yu and coworkers systematically studied the formation of OEEs between organic molecules with carbonyl/nitroxyl radical/methoxyl groups and alkali metal fluorinated sulfonylimide salts and proposed a general design methodology to prepare redox-active OEEs for RFBs (Fig. 6) 44 . Following this methodology, they found that methoxysubstituted Fc derivative remains liquid at both reduced and oxidized states.…”
Section: Eutectic Electrolytementioning
confidence: 99%
“…It can be seen that IL electrolytes are not economical and friendly, 28 aqueous electrolytes have a limited electrochemical window, 29 and organic electrolytes are usually toxic and cause environmental damage. 30,31 In contrast, eutectic electrolytes have a wide electrochemical window and superior thermal/chemical stability as well as being nontoxic and inexpensive. Meanwhile, due to the presence of complex anions and cations, the eutectic electrolytes also possess characteristics that the other electrolytes do not have, including non-flammability, easy synthesis, structural flexibility, and multi-electron reactions (Figure 1d).…”
mentioning
confidence: 99%